2012
DOI: 10.1002/pd.3891
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of first‐trimester growth restriction and low pregnancy‐associated plasma protein‐A in predicting small for gestational age at delivery

Abstract: First-trimester FGR and PAPP-A<5th percentile are associated with delivery of an SGA infant. Neither of these parameters or the combination of the two are sufficient powerful predictors of SGA to be clinically useful screening tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 29 publications
0
22
0
4
Order By: Relevance
“…Studies in the literature report relationship between low PAPP-A level and SGA infant. It has been demonstrated that there was statistically significant relationship between PAPP-A level below fifth percentile or less than 0.4 MoM and SGA or IUGR [9, 21]. Abnormal placentation may be behind low level of PAPP-A and adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in the literature report relationship between low PAPP-A level and SGA infant. It has been demonstrated that there was statistically significant relationship between PAPP-A level below fifth percentile or less than 0.4 MoM and SGA or IUGR [9, 21]. Abnormal placentation may be behind low level of PAPP-A and adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Low plasma level of PAPP-A has been recommended as biochemical marker for pregnancy with aneuploid fetus [8]. Moreover, low level has been observed in situations such as intrauterine growth restriction (IUGR) [9], preeclampsia [10], placental abruption, premature birth, fetus that is small for gestational age (SGA), and fetal death [11]. …”
mentioning
confidence: 99%
“…3,5,6,14 O aumento da utilização dos marcadores bioquímicos no primeiro trimestre levou ao acréscimo de publicações científicas que demostraram igual relação destes marcadores com recém-nascidos LIG, sobretudo a PAPP-A. [1][2][3][4][5][11][12][13][14] A Tabela 4 sumariza os dados publicados em alguns destes estudos relativamente ao valor dos marcadores bioquími-cos e odds ratio calculados.…”
Section: Discussionunclassified
“…12,13 Estudos anteriores mostram que níveis baixos de PAPP-A estão associados, como factor independente, a um risco aumentado de recém-nascidos leves para a idade gestacional (LIG) [1][2][3]5,11,14 ou seja recém-nascidos com peso inferior ao percentil 10. A subunidade β da gonadotrofina coriónica humana (β-HCG) como marcador bioquímico do primeiro trimestre, também se encontra associada a estes recém-nascidos LIG quando se apresenta com valores baixos.…”
Section: 11unclassified
See 1 more Smart Citation